2015
DOI: 10.1152/ajpheart.00289.2015
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase is involved in the development of atherosclerosis and arterial neointima formation by regulating smooth muscle cell migration

Abstract: . Soluble epoxide hydrolase is involved in the development of atherosclerosis and arterial neointima formation by regulating smooth muscle cell migration. Am J Physiol Heart Circ Physiol 309: H1894 -H1903, 2015. First published October 9, 2015; doi:10.1152/ajpheart.00289.2015.-Epoxyeicosatrienoic acids (EETs) have beneficial effects on cardiovascular disease. Soluble epoxide hydrolase (sEH) metabolizes EETs to less active diols, thus diminishing their biological activity. sEH inhibitors can suppress the progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…All rats were housed in a temperature‐controlled environment in cages containing with wood shavings as bedding (two to three per cage) with 12‐hr light/dark cycles and received food and water ad libitum. Carotid wire‐guided injury was used to model restenosis (Wang et al, ). Briefly, 0.1% heparin sodium was injected via the tail vein of rats at 0.1 mg.100 .…”
Section: Methodsmentioning
confidence: 99%
“…All rats were housed in a temperature‐controlled environment in cages containing with wood shavings as bedding (two to three per cage) with 12‐hr light/dark cycles and received food and water ad libitum. Carotid wire‐guided injury was used to model restenosis (Wang et al, ). Briefly, 0.1% heparin sodium was injected via the tail vein of rats at 0.1 mg.100 .…”
Section: Methodsmentioning
confidence: 99%
“…EETs are produced by the metabolism of arachidonic acid (substrate) through CYP-epoxygenases, which are known to play an important role in protection against ischemic injury, and act as vasodilators in arteries from the brain, intestines, skeletal muscle, heart, and aorta [4-10]. In arteries, sEH is highly expressed in endothelial cells and present lesser in smooth muscle cells [7,11,12]. Genetic deletion and inhibition of sEH protected against myocardial ischemia-reperfusion injury, improved vascular function, and decreased blood pressure in various disease models [13-16].…”
Section: Introductionmentioning
confidence: 99%
“…132 sEH inhibitors have been shown to attenuate lesion development in hyperlipidemic LDLr −/−133 or ApoE −/− mice. 134 Mechanistic studies showed that sEH inhibitors attenuated the proliferation of SMCs 135,136 and promoted reverse cholesterol transport. 133 A more recent study 137 has shown that TSN functions as a sEH inhibitor (IC 50 = 1.36 μM) by blocking the conversion of 8, 9-EET to 8, 9-DHET catalyzed by sEH in vitro.…”
Section: H Tsn As Inhibitors Of Seh 11β-hsd1 and Pcsk9mentioning
confidence: 99%